P322Understanding the multiple P-wave morphologies in paroxysmal atrial fibrillation, during sinus rhythm, using computer simulation. (18th June 2020) - Filos, D; Tachmatzidis, D; Bakogiannis, C; Mouselimis, D; Tsarouchas, A; Maglaveras, N; Vassilikos, V; Chouvarda, I
Abstract: Background: Atrial Fibrillation (AF) is the most common atrial arrhythmia. The initiation and perpetuation of AF are related to atrial remodeling affecting the electrical and structural atrial characteristics. The beat-to-beat analysis of the P-wave morphology (PWM), during sinus rhythm (SR), revealed the existence of a secondary PWM, while the proportion of the P-waves which follow the secondary morphology is higher in patients with a history of paroxysmal AF (pAF). This observation has led to the hypothesis that the multiple PWM may be the result of a transient shift in the stimulus origin, possibly within the broader anatomical region of the sinoatrial (SA) node, and it is the atrial electrical remodeling that contributes to more frequent P‐waves following a secondary morphology in patients with pAF. Purpose: To better understand the pathophysiology of AF there is a need to link different levels of analysis, in order to interpret macroscopic observations, through a surface electrocardiogram, with changes occurring at cell and tissue level. Towards this direction, computational modeling can be used as it is a non‐invasive and reproducible method of analyzing the electrical activity of the heart. Methods: The CRN atrial model was used, and a two-dimensional geometry of the atrial architecture was considered, including the major anatomical structures, like Crista Terminalis, Pectinate Muscles and Pulmonary Veins. Using existing knowledge, the CRN model was adapted to describe the ionic properties of the atrial structures as well as the electrical remodeling occurring under pAF conditions. Several scenarios were considered related to the extent of the electrical remodeled tissue and Heart Rate (HR) values. The stimulation protocol was designed as 5 stimuli originated at a specific point within the SA node area whereas the sixth stimulus originated either at the same location or 1 mm far from the previous one. The temporal variations of the atrial activation as a result of the transient shift of the sixth stimulus origin were computed. Results: In electrically remodeled tissue, the displacement of the excitation site within the SA node resulted in a significant increase of the differences in atrial activation compared to healthy tissue, and the greater the spatial extent of the remodeling the greater the differences in the completion of the electrophysiological processes. In addition, increased HR or HR variability led to the increase of the differences especially when electrical remodeling coexists. Conclusions: The observed differences in atrial substrate activation can explain the increased number of P-waves that match a secondary PWM in pAF patients during SR, while a future perspective is to use PWM as a marker to estimate the electrical remodeling extent in the atrial tissue. These results underline the need to link the macroscopic findings to the suspected microscopic electrical activity in order to better understand the pathophysiology of AF.